Competency Analysis of Student Coqnitive in Learning in Elementary Schools - Fita Nelyza (Jurnal Serambi Ilmu, 2024)
The principle of the guided inquiry learning process interaction emphasizes the interaction between students and teachers, and between students and the environment. Learning as an interaction process means placing the teacher not as a source of learning, but as a regulator of the environment or regulator of the interaction itself, the teacher as the questioner. The purpose of this study was to determine how the effect of the guided inquiry model on improving student conitive comptency. This research was conducted in the even semester of the 2017/2018 academic year, using the pre-experimental design method through one group pretestposttest design. This research was carried out in three stages, namely: giving a pretest questionnaire to obtain the average score of student co-technician competencies, implementing the guided inquiry learning model, and giving the final test (posttest) after learning. The subjects of this study were fourth grade students consisting of 14 male students and 13 female students. The data collection techniques used were observation and tests. Observations were made to observe student activities, while the test consisted of preliminary and final tests used to measure learning success. The assessment instrument consists of an observation sheet filled out by the observer and the test questions consisting of 10 questions. Furthermore, student learning outcomes are processed using the Gain formula (g). Based on the research results obtained, 11 students obtained a Gain value of 0.75 in the high category, and 16 students obtained a Gain value of 0.60 in the moderate category. The overall average value of learning outcomes is 0.65 in the medium category. Thus, it can be concluded that the application of the guided inquiry model can affect science student coqinitive.